Usability Assessment of Secure Messaging for Clinical Document Sharing between Health Care Providers and Patients - Jahn, Michelle A.; Porter, Brian W.; Patel, Himalaya; Zillich, Alan J.; Simon, Steven R.; Russ, Alissa L. (Applied Clinical Informatics, 2018)
Background Web-based patient portals feature secure messaging systems that enable health care providers and patients to communicate information. However, little is known about the usability of these systems for clinical document sharing.Objective This article evaluates the usability of a secure messaging system for providers and patients in terms of its ability to support sharing of electronic clinical documents.Methods We conducted usability testing with providers and patients in a human–computer interaction laboratory at a Midwestern U.S. hospital. Providers sent a medication list document to a fictitious patient via secure messaging. Separately, patients retrieved the clinical document from a secure message and returned it to a fictitious provider. We collected use errors, task completion, task time, and satisfaction.Results Twenty-nine individuals participated: 19 providers (6 physicians, 6 registered nurses, and 7 pharmacists) and 10 patients. Among providers, 11 (58%) attached and sent the clinical document via secure messaging without requiring assistance, in a median (range) of 4.5 (1.8–12.7) minutes. No patients completed tasks without moderator assistance. Patients accessed the secure messaging system within 3.6 (1.2–15.0) minutes; retrieved the clinical document within 0.8 (0.5–5.7) minutes; and sent the attached clinical document in 6.3 (1.5–18.1) minutes. Although median satisfaction ratings were high, with 5.8 for providers and 6.0 for patients (scale, 0–7), we identified 36 different use errors. Physicians and pharmacists requested additional features to support care coordination via health information technology, while nurses requested features to support efficiency for their tasks.Conclusion This study examined the usability of clinical document sharing, a key feature of many secure messaging systems. Our results highlight similarities and differences between provider and patient end-user groups, which can inform secure messaging design to improve learnability and efficiency. The observations suggest recommendations for improving the technical aspects of secure messaging for clinical document sharing.
Keywords: personal health records; secure messaging; communication; interfaces and usability; electronic health records and systems